The characterization of a thermostable and cambialistic superoxide dismutase from thermus filiformis - Mandelli, F.; Franco Cairo, J. P L; Citadini, A. P S; Büchli, F.; Alvarez, T. M.; Oliveira, R. J. [UNESP]; Leite, V. B P [UNESP]; Paes Leme, A. F.; Mercadante, A. Z.; Squina, F. M. (Oxford University Press (OUP), 2013)
The superoxide dismutase (TfSOD) gene from the extremely thermophilic bacterium Thermus filiformis was cloned and expressed at high levels in mesophilic host. The purified enzyme displayed approximately 25 kDa band in the SDS-PAGE, which was further confirmed as TfSOD by mass spectrometry. The TfSOD was characterized as a cambialistic enzyme once it had enzymatic activity with either manganese or iron as cofactor. TfSOD showed thermostability at 65, 70 and 80°C. The amount of enzyme required to inhibit 50% of pyrogallol autoxidation was 0·41, 0·56 and 13·73 mg at 65, 70 and 80°C, respectively. According to the circular dichroism (CD) spectra data, the secondary structure was progressively lost after increasing the temperature above 70°C. The 3-dimensional model of TfSOD with the predicted cofactor binding corroborated with functional and CD analysis. © 2013 The Society for Applied Microbiology.
Keywords: 3-D model; Cambialistic enzyme; Circular dichroism; Nitroblue tetrazolium; Pyrogallol autoxidation; iron; manganese; pyrogallol; superoxide dismutase; clone; enzyme activity; gene expression; inhibition; mass spectrometry; thermophilic bacterium; three-dimensional modeling; amino acid sequence; autooxidation; circular dichroism; controlled study; molecular cloning; nonhuman; polyacrylamide gel electrophoresis; protein expression; protein purification; protein secondary structure; thermostability; Thermus; Thermus filiformis